Influence of external magnetic field on intensity and directivity of EUV radiation from high-current pulse plasma diode - Borgun, Ie.V.; Azarenkov, N.A.; Hassanein, A.; Tseluyko, A.F.; Maslov, V.I.; Ryabchikov, D.L.; Grechko, Y. (Вопросы атомной науки и техники, 2012)
This work is devoted to evaluate the influence of the additional external magnetic field on dynamics of the radiation in the extreme ultraviolet (EUV) range from multi-charged tin plasma of high-current pulse diode. Investigations have shown that the use of an additional external magnetic field has improved the stability of the plasma diode, enhanced the intensity of radiation, and changed the radiation profile. Работа посвящена оценке влияния дополнительного внешнего магнитного поля на динамику излучения в диапазоне вакуумного ультрафиолета (ВУФ) из многозарядной плазмы олова сильноточного импульсного диода. Исследования показали, что использование внешнего магнитного поля позволяет улучшить стабильность работы плазменного диода, повысить интенсивность излучения и изменять диаграмму направленности излучения. Робота присвячена оцінці впливу додаткового магнітного поля на динаміку випромінювання в діапазоні екстремального вакуумного ультрафіолету (ВУФ) з багатозарядної плазми олова сильнострумного імпульсного діодa. Дослідження показали, що використання зовнішнього магнітного поля дозволяє покращити стабільність роботи плазмового діодa, збільшити інтенсивність випромінювання та змінювати діаграму спрямованості випромінювання.